La declaratoria de inconstitucionalidad de normas por conexidad en Ecuador (Tema Central) - Polo Pazmiño, Esteban Javier (2022)
This article addresses a novel modality of constitutional review applied in Ecuadorian constitutional justice: the faculty of the Constitutional Court to declare related statutes unconstitutional ex officio. As its scope remains unclear, it is due to the ambiguity of the legal standards that govern this mechanism, its recent addition to the system, and the lack of studies about it. Firstly, the objective of this essay is to analyze the content of legislation and jurisprudence about the declaration of unconstitutionality of related statutes for understanding its principal attributes in the Ecuadorian legal context. Secondly, the purpose is to comprehend the main critical points that contribute to the difficulties associated with the utilization of this faculty. For that matter, the focus of the analysis will be the applicable rules, emphasizing case law. Even though the Constitutional Court has applied this mechanism numerous times, it has not answered many doubts about its implementation. The development of guidelines for the implementation of this faculty has only begun since issuing judgment 1024-19-JP/21 in 2021.